Analisa Kuantitas Dan Kualitas Air Sumur Bor Di Desa Tihang Kecamatan Lengkiti Kabupaten Ogan Komering Ulu - Azwar Azwar (Jurnal Tekno Global, 2021)
This research discusses the quantity and quality of clean water that has been used by the community in Tihang Village, Lengkiti District, Ogan Komering Ulu Regency. In the daily process, the local community uses a lot of drilled well water to facilitate their daily activities. There are 7 Drilled Well points in Tihang Village, but only 3 Drilled Well points are active. Tihang Village has a population of 1663 people (2016 statistical data center). Therefore, Tihang Village is included in the rural category with water consumption of 50 liters / person / day. The borehole water distribution system is carried out by flowing the air from the well using the intake pump to the booster, the distribution pump discharge is determined based on fluctuations in water use in one day schedule. It turns out that after conducting a simple water test that has reached the community, the pH of the water passes into the requirements stipulated under Permenkes No. 32 of 2017 concerning Environmental Health Quality Standards and Water Health Requirements. The quality of water from these three sources is quite good because the water test results simply show that the water is odorless. And from the results of laboratory test analysis, both Physical and Chemical, the clarity is sufficient because the differences are not too far away. The highest pH was 7.40 in Hamlet V, while the pH of the three hamlets was only 1% different. However, the results of water from Dusun III, IV and V are good enough to be used as raw material for drinking water because the pH is neutral and non-toxic. After a simple test of water pH in Tihang Village, namely vilage III, IV and V passed the applicable requirements Keywords: Quantity, Quality, Drilled Well Water.